Study of Static Progressive Flexion Mitt on Finger Flexion Improvement for Stiff Hands - Zhongfei BAI; Xiaoyu SHI; Weili XIA; Chuanping LI; Huifang WANG (康复学报)
Objective:To observe whether the effect of progressive flexion mitt on improving finger flexion function has significantly differences for stiff fingers after traumatic injury on the basis of conventional therapy.Methods:Non-randomly recruited 19 subjects with stiff fingers into each group, experimental group and control group. The control group received conventional treatment and self stretch, and the experimental group received the treatment of static progressive flexion mitt besides the conventional treatment for four weeks. Passive and active range of motion of metacarpal-phalange joints, proximal inter-phalange joints and distal inter-phalange joints were assessed before and after the intervention.Results:The improvements on passive range of motion of metacarpal-phalange joints in experimental group were better than those in control group (P<0.05), the improvments on active range of motion of metacarpal-phalange joints were also significantly different between two groups (P<0.05). Experimental group and control group showed no significant differences on passive and active range of motion improvement on proximal inter-phalange joints and distal interphalange joints (P>0.05). The improvements on passive range of motion on metacarpal-phalange joints had the highest correlation with the improvement of active range of motion of metacarpal-phalange joints (γ=0.848, P<0.05).Conclusion:The static progressive flexion mitt can be used as an assistive therapy to improve passive and active range of motion on metacarpal-phalange joints for stiff hand.